The Frobenius endomorphism to Elliptic Curves and same properties - Apaza Rodriguez, Jaime Edmundo (2023)
In this work we present the Frobenius endomorphism for Elliptical Curves defined over finite fields and some of their properties relative to their kernel and the condition of separability.